Critical review of literature on corporate governance and the cost of capital:the value creation perspective - Ab. Rashid, Hafiz Majdi (African Journal of Business Management, 2010)
Corporate governance encompasses a broad spectrum of mechanisms intended to mitigate agency risk by increasing the monitoring of managements’ actions, limiting managers’ opportunistic behaviour, and improving the quality of firms’ information flows. A torrent of literature explains that corporate governance mechanisms are able to enhance a firm’s value. A firm’s value is commonly measured using either market or accounting performance measures. Alternatively, a value is created when a firm enjoys a reduction in its cost of capital. Theoretically, firms that have robust monitoring devices including strong protection of stakeholders’ rights will be able to limit the extent of managerial power abuse and prudently allocate resources. This type of firm should have lower risk and access to cheaper sources of capital than other firms. This paper aimed to provide a critical review of literature on the effect of corporate governance on the cost of capital emphasising on the value creation perspective of corporate governance.